Missile Defences and Asian-Pacific Security - Mazarr, Michael J. author. aut Link
XII, 226 p.
Keywords: An in-depth study of the military, economic, and political implications of the strategic and tactical missile defences for the Asian-Pacific region. It offers recent research on the status of SDI and Asian-Pacific countries and offers an introduction to the SDI debate and Europe.